X and Y chromosome-bearing spermatozoa are equally able to uptake and internalize exogenous DNA by sperm-mediated gene transfer in swine. (February 2016) - Zaniboni, Andrea; Spinaci, Marcella; Zannoni, Augusta; Bernardini, Chiara; Forni, Monica; Bacci, Maria Laura
Abstract: Since proteomic differences between male X/Y chromosome-bearing gametes have recently been described, a question has been raised: could these differences be responsible for different behavior between X and Y chromosome-bearing spermatozoa during the binding and internalization of exogenous DNA in the swine species? In order to investigate this hypothesis, our group studied the process of the uptake and internalization of exogenous DNA in X and Y chromosome-bearing sperm sub-populations. No significant differences were found between sperm types in both the uptake and internalization of exogenous DNA. The quantity of internalized exogenous DNA was significantly lower than that of the uptaken DNA. In conclusion, our results showed that X and Y chromosomes-bearing spermatozoa have the same binding capacity and internalization of DNA, and the proteomic differences between them do not seem to interfere with these complex processes. Highlights: Our group has produced genetically modified (GM) pigs since many years through SMGT. We have noticed a not significant positive trend in the birth of GM male piglets. We investigated if X and Y sorted sperms differentially internalized exogenous DNA. Data obtained from qPCR showed no significant differences among X and Y sperms. X and Y sperms equally internalize exogenous DNA during SMGT.